2014
DOI: 10.3109/02699052.2014.989402
|View full text |Cite
|
Sign up to set email alerts
|

Anxious attachment style and hopelessness as predictors of burden in caregivers of patients with disorders of consciousness: A pilot study

Abstract: These data suggest that caregivers need psychological assessment and support in order to keep under control the level of burden and to help themselves be a better resource for their relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…These results suggest to carefully evaluate caregivers' burden to properly answer to caregivers' needs, especially in case of need for information and communication (13). In this regard, a recent study demonstrated that preoccupied attachment style and hopelessness together play a relevant role in predicting burden variability (14).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest to carefully evaluate caregivers' burden to properly answer to caregivers' needs, especially in case of need for information and communication (13). In this regard, a recent study demonstrated that preoccupied attachment style and hopelessness together play a relevant role in predicting burden variability (14).…”
Section: Introductionmentioning
confidence: 99%
“…Of course, this issue did not disappoint them completely and the caregivers often experienced a fluctuation of hope. 53 …”
Section: Discussionmentioning
confidence: 99%
“…Moules and Chandler found that the relative's psychological distress was associated with the level of needs' satisfaction [7]. A recent study on the caregivers of patients with disorders of consciousness found that the combination of a preoccupied attachment style and a high degree of hopelessness predicted 49% of the total variability of burden [31]. In our study, the presence of anxiety and depressed feelings also seems to be related to the degree of needs' satisfaction, as the relatives with lower quality of life were also the ones with a higher percentage of unmet needs.…”
Section: Discussionmentioning
confidence: 99%